The complete chloroplast genome sequence of Calanthe delavayi (Orchidaceae), an endemic to China - Yan-Qiong Chen; Si-Ren Lan; Zhong-Jian Liu; Jun-Wen Zhai (Mitochondrial DNA. Part B. Resources, 2019)
Calanthe delavayi, an endemic terrestrial orchid distributed in southwestern China. In this study, the complete chloroplast genome (cpDNA) sequence of C. delavayi was determined from Illumina pair-end sequencing data. With a total length of 150,181 bp in length and includes two inverted repeat regions (IRs) of 23,721 bp each, which were separated by a large single copy region (LSC) 87,392 bp and a small single copy region (SSC) 18,693 bp. The chloroplast genome contained 135 genes, including protein-coding genes, tRNA genes, and eight rRNA genes. Phylogenetic analysis indicates that C. delavayi, C. davidii, and C. triplicata cluster together, placed them within tribe Collabieae.